The Influence of TikTok EWOM on Purchase Intentions for The Originote Skincare Products - Hidayah, Riski Taufik; Adriansyah, Irfan; Utami, Eristy Minda (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
The aim of this research is to examine the impact of electronic word-of-mouth (eWOM) on TikTok regarding consumer purchase intentions for The Originote skincare products. The research targeted TikTok users interested in The Originote skincare products, with the total population being unknown. Utilizing the Cochran formula, the study sampled 273 respondents through purposive sampling to complete the questionnaire. The raw data were processed and analyzed utilizing SPSS version 23. The results reveal that The purchase intention for The Originote skincare products is significantly influenced by the quality of eWOM on TikTok. Similarly, the credibility of electronic word-of-mouth influences purchase intention, and The volume of electronic word-of-mouth on TikTok also exerts a significant influence on consumers' purchase intentions, Furthermore, the quality, credibility, and quantity of electronic word of mouth on the TikTok application collectively exerts a simultaneous influence on the purchase intention for The Originote skincare products. Given the rapid expansion of Indonesia's skincare industry and the growing importance of social media platforms such as TikTok, understanding how eWOM quality, credibility and quantity influence purchase intentions for The Originote skincare products, is critical.